The role of leverage as mediator the effect of male CEO masculinity face on research & development - Indra Prasetyo; Nabilah Aliyyah; Esa Wahyu Endarti; Nur Fadjrih Asyik; Rusdiyanto Rusdiyanto; Dian Anita Nuswantara; Gazali Gazali (Cogent Business & Management, 2023)
This study aims to prove the support of Agency Theory and Behavioral Consistency Theory as a solution to explain the role of leverage in mediating the influence of male CEO masculinity on research and development. This study uses a quantitative approach with a population and research sample using companies on the Indonesia Stock Exchange in 2017-2021. This study collects facial images identified as male CEOs from data on the Indonesia Stock Exchange website and company websites and utilizes Google search. The data analysis method in this study uses Structural Equation Modeling which connects theories, concepts and data that can be applied to research variables. The findings explain that decreasing and increasing leverage has an impact on increasing and decreasing the masculinity value of male CEOs as well as increasing and decreasing the value of research and development. The implications of the results of this research can assist the Indonesian Institute of Accountants in developing Financial Accounting Standards No. 19 in Indonesia. The theoretical implications of the results of this study can be explained through Agency Theory, Behavioral Consistency Theory and Upper Echelon Theory. The policy implications of the results of this study can provide empirical evidence that the higher the face value of masculinity for male CEOs has an impact on increasing leverage and research and development costs, conversely the lower face value of masculinity for male CEOs has an impact on increasing the value of leverage as well as research and development, and leverage mediates the effect of face male CEO masculinity on research and development costs.
Keywords: G02; G32; G34; M1; Z1; 650; CEO Male; Leverage; Masculinity; R&D; SEM; Stata